أثر استخدام الفيديو المتحرّك في ترقية مهارة الكلام لطلاب مدرسة خزانة كباجيكان المتوسطة الإسلامية تانجيرانج - Rusydah, Afiyah Nur; Edidarmo, Toto (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2025)
AbstractThis research aims to examine the effect of using animated videos on students' speaking skills and to identify the supporting and inhibiting factors in teaching speaking skills through animated videos. The study employed a mixed-method approach that combines quantitative and qualitative research. The population in this study consisted of all seventh-grade students, with a research sample of 71 students divided into experimental and control groups. Data collection methods for the quantitative research included pre-tests and post-tests, while qualitative data were gathered through interviews and observations. Data analysis for the quantitative research employed t-tests. The results showed that the average post-test score for the experimental group was 81.6, compared to 72.4 for the control group. Data analysis using the Independent Sample T-test revealed a significant difference between the experimental and control groups, with a p-value of 0.000 (< 0.05), indicating that the alternative hypothesis was accepted and the null hypothesis was rejected. This demonstrates that the use of animated videos has a significant effect on speaking skills. Supporting factors in the learning process included increased student interest, support from the school environment, and ease of access to educational media. Inhibiting factors included differences in students' educational backgrounds and the need for additional time. This study explores the use of animated videos as a novel tool to improve intermediate-level Arabic speaking skills. It examines both the impact of these videos and the factors influencing the learning process. However, limitations include a small sample size limited to seventh-grade students and a short study duration, making it challenging to assess long-term effects.Keywords: Speaking Skills, Learning Media, Animated Videos. مستخلص البحثيهدف هذا البحث إلى أثر استخدام الفيديو المتحرك على كفاءة الطلاب في مهارة الكلام ٢) العوامل الداعمة والعائقة في تعليم مهارة الكلام باستخدام الفيديو المتحرك. استخدم البحث المختلط بين طريقة تجمع البحث الكمي والنوعي. كان عدد السكان في هذا البحث جميع طلاب في الصف السابع مع عينة البحث التي تتكون من ٧١ طالبا وتنقسم إلى المجموعة التجريبية والضابطة. طريقة جمع البيانات للبحث الكمي هي الاختبار القبلي والبعدي، بينما تتم مقابلة البحث النوعي والمراقبة. طريقة تحليل البيانات في البحث الكمي هي الاختبارت. أظهرت النتائج أن متوسط درجة الاختبار البعدي للمجموعة التجريبية كان 81،6 بينما كان متوسط المجموعة الضابطة 72،4. وأظهر تحليل البيانات باستخدام اختبار العينة ت المستقل فرقا كبيرا بين المجموعات التجريبية والسيطرة بقيمة 0،000 (< 0،05)، مما يعني أن الفرضية البديلة مقبولة وأن الفرضية الصفرية مرفوضة. هذا يوضح أن استخدام مقاطع الفيديو المتحرك لها تأثير على مهارة الكلام. وتشمل العوامل الداعمة للتعلبم زيادة اهتمام الطلاب، والدعم من البيئة المدرسية، وسهولة الوصول إلى الوسائل التعليمية. العوامل العائقة هي الاختلافات في الخلفيات التعليمية للطلاب وتتطلب المزيد من الوقت. يبحث هذا البحث في استخدام مقاطع الفيديو المتحركة كأداة جديدة لتحسين مهارات التحدث باللغة العربية على المستوى المتوسط. كما يستكشف تأثير هذه المقاطع والعوامل المؤثرة في عملية التعلم. ومع ذلك، يقتصر البحث على عينة صغيرة من طلاب الصف السابع وفترة قصيرة، مما يصعب تقييم التأثيرات طويلة المدى.الكلمات المفتاحية: مهارة الكلام، الوسيلة التعليمية، الفيديو المتحرك.